PERGESERAN TERITORI SEBAGAI BENTUK ADAPTASI PADA TERAS RUMAH AKIBAT PENGEMBANGAN PARIWISATA DI KAMPUNG PELANGI, KOTA SEMARANG - Vincentia Aprilia Ratnasari; Happy Ratna Sumartinah; Dewi Septanti (Jurnal Arsitektur ARCADE, 2020)
Abstract: Tourism has the opportunity to be able to give a good influence on several aspects (economic, social, cultural, and environmental), so it makes one of the strategies of the Semarang City government to be used to solve the problems of slums in Kampung Wonosari. Kampung Wonosari which was changed into a tourist village, and changed its name to Kampung Pelangi. In addition to the positive effects obtained, but there are also negative effects due to changes in the function of the village. One of the negative influences is that there is a shift in territorial occupancy because people have to share their space with visitors. From this phenomenon, this research will raise the issue of territorial shift as a form of adaptation due to the development of tourism in the village. Based on these problems the purpose of this study is to determine the form of territory shifting from the form of adaptation that occurred. This research method uses a descriptive qualitative method. So we get realistic results from the object of shifting territory on the porch as a form of adaptation to follow the development of the village into a tourist attraction.